Pembinaan Baca Al Quran Pada Lansia Melalui Program Pondok Ramadhan Di Masjid Cukir Diwek Jombang - An Nahdliyah, Khumairoh; Riza, Julianne Kamelia; Ya’cub, Mihmidaty; Wijono, Hani Adi (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2024)
Teaching the elderly to read the Koran is a challenge and an opportunity to help them deepen their spirituality. Elderly people often face various obstacles such as decreased vision, decreased memory, and difficulty in learning new things. However, with the right methods, this process can be a meaningful and rewarding experience. This service aims to analyze learning to read the Koran in the elderly. The methods used in this learning are class grouping, the Baghdadi Method, and the Slow Tartil Method. The results of the service show that teaching reading the Qur'an to the elderly includes Teaching reading the Qur'an to the elderly is a challenge and an opportunity to help them deepen their spirituality. Elderly people often face various obstacles such as decreased vision, decreased memory, and difficulty in learning new things. However, learning to read the Koran can be carried out well and smoothly. The results obtained from coaching to read the Al Quran are recognition of hijaiyah letters, correct pronunciation and pronunciation of hijaiyah letters, and skills in reading the Al Quran correctly.